Aspects of cathodic stripping voltammetry at the hanging mercury drop electrode and in non-mercury disposable sensors - Fogg, Arnold G.; Zanoni, M. Valnice B. [UNESP]; Barros, Aquiles A.; Rodrigues, Jose A.; Birch, Brian J. (My University, 2000)
Cathodic stripping voltammetry (CSV) and accumulation at the hanging mercury drop electrode are reviewed briefly. Proposals in a recent IUPAC technical report are considered. Three recent developments in CSV are discussed: the adaptation of CSV methods developed for use with the hanging mercury drop electrode for use with screen-printed carbon electrodes in disposable sensors, the use of reactive accumulation, and the chemometric use of kinetic methods of determination with pulse methods in CSV.
Keywords: Cathodic stripping voltammetry; Reactive accumulation; Reduction kinetics; Screen-printed carbon electrodes